(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This article is devoted to the identification of morphological changes occurring in the histotopography of the ovaries of 12-month-old children. As a material, the ovaries of girls whose abdomen died from asphyxia and pneumopathy were studied by methods of general histology, histochemistry and morphometry. It is noted that in the cortical layer of the ovary of newborns, rudimentary eggs are located in a dense state, follicular structures are formed as a result of the proliferation of granulose cells in the areas bordering the stratum corneum, and between them, i.e. in the interstitial, there are pregranular and celemic cells of different densities. From the earliest postpartum period in infants, destruction and atresia of part of the embryonic eggs that perform reproductive function in the ovary, granulosis and proliferation of cells of the uterine tissue in the intermediate tissue occur.